Histopathologic tumor response after induction chemotherapy and stereotactic body radiation therapy for borderline resectable pancreatic cancer - Chuong, Michael D.; Frakes, Jessica M.; Figura, Nicholas; Hoffe, Sarah E.; Shridhar, Ravi; Mellon, Eric A.; Hodul, Pamela J.; Malafa, Mokenge P.; Springett, Gregory M.; Centeno, Barbara A. (Journal of Gastrointestinal Oncology; Vol 7, No 2 (April 01, 2016): Journal of Gastrointestinal Oncology, 2015)
Background: While clinical outcomes following induction chemotherapy and stereotactic body radiation therapy (SBRT) have been reported for borderline resectable pancreatic cancer (BRPC) patients, pathologic response has not previously been described. Methods: This single-institution retrospective review evaluated BRPC patients who completed induction gemcitabine-based chemotherapy followed by SBRT and surgical resection. Each surgical specimen was assigned two tumor regression grades (TRG), one using the College of American Pathologists (CAP) criteria and one using the MD Anderson Cancer Center (MDACC) criteria. Overall survival (OS) and progression free survival (PFS) were correlated to TRG score. Results: We evaluated 36 patients with a median follow-up of 13.8 months (range, 6.1-24.8 months). The most common induction chemotherapy regimen (82%) was GTX (gemcitabine, docetaxel, capecitabine). A median SBRT dose of 35 Gy (range, 30-40 Gy) in 5 fractions was delivered to the region of vascular involvement. The margin-negative resection rate was 97.2%. Improved response according to MDACC grade trended towards superior PFS (P=061), but not OS. Any neoadjuvant treatment effect according to MDACC scoring (IIa-IV vs. I) was associated with improved OS and PFS (both P=0.019). We found no relationship between CAP score and OS or PFS. Conclusions: These data suggest that the increased pathologic response after induction chemotherapy and SBRT is correlated with improved survival for BRPC patients.